2014
DOI: 10.4028/www.scientific.net/amr.997.526
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization of Petroleum Coke via Alkali Calcination

Abstract: Alkali desulfurization of petroleum coke is an important technology, can improve the performance of the final products of petroleum coke, while reducing air pollution. This paper studied the conditions for desulfurization of calcined petroleum coke using NaOH solid powders. The experimental results show that, the grain size in the range of experiment did not seem to influence desulphurization. With the increase of temperature, adding alkali coke ratio, reaction time, desulfurization of petroleum coke rate incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Wang et al [ 38 ] found that the desulfurization effect of petroleum coke has little correlation with the particle size of petroleum coke. However, Pintowantoro et al [ 43 ] found that, as the particle size of petroleum coke decreased, the desulfurization effect increased, and a particle size of 100 mesh was sufficient to destroy the chemical bonds of sulfur compounds in petroleum coke.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [ 38 ] found that the desulfurization effect of petroleum coke has little correlation with the particle size of petroleum coke. However, Pintowantoro et al [ 43 ] found that, as the particle size of petroleum coke decreased, the desulfurization effect increased, and a particle size of 100 mesh was sufficient to destroy the chemical bonds of sulfur compounds in petroleum coke.…”
Section: Resultsmentioning
confidence: 99%
“…Alkali metal compounds such as potassium hydroxide (KOH) and sodium hydroxide (NaOH) react with organic sulfur, sulfur salts, and sulfur-containing gases in petroleum coke at higher temperatures to effectively remove sulfur from petroleum coke [ 37 ]. Wang et al [ 38 ] utilized NaOH to study the desulfurization performance of petroleum. The experiment, conducted under inert atmospheric conditions, involved an initial sulfur mass fraction of 6.50%, an alkali-to-petroleum-coke ratio of 50%, a temperature of 500 °C, and a reaction time of 2 h. The results indicated a 98.1% desulfurization rate of petroleum coke.…”
Section: Introductionmentioning
confidence: 99%
“…Desulphurisation of petroleum coke via calcination in the presence of an excess amount of alkali is known to reduce the sulphur content of petroleum coke substantially [11,12]. In a recent development, researchers found that with an alkali-to-coke ratio of 2, a reaction temperature of 500 °C, and a reaction time of 2 h, the desulphurisation of petroleum coke reached 98% when NaOH powder was used as an alkali source [13]. Although the alkali calcination technique reduces sulphur content in petroleum coke to a large extent, the method is not economically viable due to the stoichiometric use of caustic.…”
Section: Introductionmentioning
confidence: 99%